SERVICE QUALITY DIMENSIONS AND PATIENT SATISFACTION: A TWO-SIDED EMPIRICAL APPROACH - Khayam Ali Shah, Syed; Ul Hadi, Noor (Journal of Ayub Medical College Abbottabad, 2019)
Background: The present study attempts to investigate the impact of service quality dimensions (perceptions of patients as well as service providers) on patient satisfaction in public sector hospitals of Khyber Pakhtunkhwa province. The need to conduct research in this area is due to the growing importance of service quality in the healthcare sector. Thus, examining the two-sided role of service quality dimensions on patient satisfaction in the Province of KP is the main rationale behind the present study. Methods: The data was conveniently collected from a sample of 600 patients and 200 service providers from six district headquarter hospitals. The hypothesized relationships were tested via multiple regression analysis with the application of SPSS-23. Results: Interestingly, divergent results were found from both perspectives. Six dimensions of service quality were found critical by the patients for their satisfaction whereas, only one dimension was found to be critical for patient satisfaction from service providers' perspective signifying that service providers are not meeting the expectations of the patients. Conclusions: The present study suggests the formulation of a sound patient-centred strategy in which patients are placed as value co-creators to increase their satisfaction with the services offered in public hospitals at KP Province, Pakistan. The study also discussed limitations, implications and future research directions. Keywords: patient satisfaction; service quality; health sector; Khyber Pakhtunkhwa